HOW EFFECTIVE IS THE IMPLEMENTATION OF A CIRCULAR ECONOMY IN THE EUROPEAN UNION (27) TOWARDS THE CLIMATE CHANGE RATE? : A PREVALENCE ANALYSIS WITH EUROSTAT DATA - Setya Navyando, Varelino (PEOPLE: International Journal of Social Sciences, 2024)
Circular economy, a sustainable approach to resource management, is gaining attention amid escalating climate change concerns from the rise of greenhouse gas emissions. The problem lies in the true impact of using a circular economy in building climate resilience. In this study, I analyze Eurostat data from 27 European Union countries using multivariate regression statistics to unveil the relationship between circular economy practices and greenhouse gas emissions. Employing a robust methodological framework, my findings reveal a significant correlation between circular economy adoption and reducing greenhouse gas emissions. These insights hold implications for policymakers, advocating for the integration of circular economy strategies to enhance climate resilience and shape effective climate policies for European Union policymakers.